The Implementasi Metode Ummi Dalam Pembelajaran Turjuman Al-Qur’an Jilid 1 dan 2 - Rahmawati, Sri Tuti; Rotullutfiah, Zah (Prodi Pendidikan Keagamaan Islam, 2024)
The Ummi method is one of the methods of learning the Qur'an in which there is learning turjuman Al-Qur'an volumes 1 and 2 which discuss prayer recitation. the purpose of this study is to determine the implementation of learning, the supporting and inhibiting factors of learning, and the impact of learning Turjuman Al-Qur'an volumes 1 and 2 of the Ummi method at Mutiara Hikmah Al-Qur'an Elementary School Bekasi. The type of research used in this study is descriptive qualitative research. The data collection was obtained through observation, interview, and documentation techniques. Data analysis in this study is by data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Ummi method in learning Turjuman Al-Qur'an volumes 1 and 2 went well because in its learning, Mutiara Hikmah Bekasi Al-Qur'an Elementary School applied the strengths of the Ummi Foundation, namely the existence of quality methods, qualified teachers, and quality systems.